P493 The synthetic glycan KB295 optimises microbiome composition and function in ulcerative colitis: Results from a proof of principle human study. (21st January 2022) - Meisner, J; Miller, K; Lee, J; Jose, A; Giuggio, M; McComb, M; Humphries, E; Rosini, M; Wingertzahn, M; Shanahan, F; van Hylckama Vlieg, J E T; Dowling, M
Abstract: Background: Ulcerative colitis (UC) pathogenesis involves genetic susceptibility, immune-mediated tissue injury, and gut microbiota disturbances. Most approved therapies modify host immunity, rather than directly targeting the microbiota. Faecal microbiota transplantation provides encouraging evidence for the therapeutic potential of gut microbiome modulation. Gastrointestinal tract bacteria are ecologically differentiated by their ability to use specific glycans as growth substrates, making glycans a promising and safe alternative to target the microbiome. To explore this, we used an ex vivo faecal microbiota culture system to identify a synthetic glycan (KB295) with desirable microbiological activity and conducted a proof of principle study (NCT04508413) of safety and tolerability of KB295 in patients with UC. Methods: In ex vivo studies, faecal microbial communities from healthy subjects were incubated anaerobically (negative control) ± KB295. Taxa counts from shotgun metagenomic sequencing data were used to evaluate microbial response to KB295. Short-chain fatty acid (SCFA) levels were also assessed. KB295 was evaluated in an open-label single-arm study in adult patients with mild to moderate UC. KB295 was ingested over an 8-wk period. Objectives included KB295 safety (primary) and effect on gut microbiota composition and faecal biomarkers. Results: In ex vivo studies, KB295 increased SCFA levels across 10 faecal samples to a median of 47.0 vs 15.2 mM with negative control, including increases in acetate, propionate, and butyrate levels. Metagenomic sequencing showed pathobiont depletion in the family Enterobacteriaceae with KB295 to a median relative abundance of 10.8% vs 38.2% with negative control. Pathobiont depletion was associated with enrichments of diverse genera in the phyla Bacteroidetes and Firmicutes . In patients with UC (n=12), KB295 was well tolerated with generally mild adverse events (AEs). The most frequently occurring AEs were bowel habit changes, flatulence, and headache. Median faecal calprotectin and lactoferrin levels decreased by 69.0% (n=11) and 86.0% (n=6), respectively, from screening to end of the KB295 intake. Consistent with our ex vivo results, of the patients for whom we have data to date, the relative abundance of the faecal pathobiont family Enterobacteriaceae decreased in 5 of 5 participants, and the commensal genus Parabacteroides was enriched in 4 of 5 participants. Conclusion: Our results establish a proof of principle for the glycan modulation of gut microbiome composition and function and provide insight into the potential utility of this strategy in patients with UC. The safety and tolerability of KB295, along with evidence of reduced inflammation, support a phase 2 study, which is planned.